PENGARUH KOMPETENSI DAN INDEPENDENSI TERHADAP KUALITAS AUDIT DENGAN ETIKA AUDITOR SEBAGAI VARIABEL MODERASI - Mariyanto, Bondan Fajar; Praptoyo, Sugeng (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
This research is meant to analyze the influence of competency and independency of auditor to the audit qualitywith the audit ethics as moderating variable. This research is quantitative. The population of this research isPublic Accountant Firm profession auditor who supports the market capital in East Java. The selection ofresearch samples has been done by performing purposive sampling with the criteria auditors who have theirpublic accountant office license . therefore Public Accountant Firm profession auditors who support the marketcapital in East Java and 8 Public Accountant Firms and 40 Public Accountant Firms observation data have beenselected as samples. The result of this research shows that competency, independency, and audit ethics havesignificant influence to the audit quality. It indicates that when the competency and independency which isowned by the auditor is high, it will become an ethics to provide qualified audit.Keywords: competency, independency, audit ethics, audit quality.